MIXED PULMONARY INFECTION IN A PATIENT WITHSUCCESSFULLY TREATED RECURRENCE OF FOCALSEGMENTAL GLOMERULOSCLEROSIS ON KIDNEYALLOGRAFT - Severova Andreevska, Galina; Karanfilovski, Vlatko; Suleyman, Sabir; Shterjova Markovska, Zhaklina; Nikolov, Igor; Trajcheska, Lada; Taleska, Ana; Karanfilovikj, Angela; Filipovski, Stefan; Gjorgjievski, Nikola; Dzambazovska Trajkovska, Vanja; Andonovska, Biljana; et al. (Uniunea Medicala Balcanica, 2024)
Introduction. Recurrence of focal segmental glomerulosclerosis (FSGS) in patients with a kidney transplant (KTx) is a challenging issue. Pulmonary infections can further complicate the clinical course of these patients. Case presentation. A 36-years-old female with kidney failure due to FSGS had KTx from a living-related donor in 2017, with stable graft function during the follow-up. In 2021, the patient presented with proteinuria and increased serum creatinine. Renal biopsy demonstrated recurrence of FSGS in kidney allograft. She was treated with Rituximab combined with plasma exchanges and achieved complete remission. In 2023, the patient was admitted due to 10-days history of weakness, fever and productive cough with hemoptysis. The computed tomography scan of the lungs revealed bilateral ground-glass opacities with cavitary lesion. The bronchoalveolar lavage and immunofluorescence test for detection of atypical pulmonary pathogens were positive for Acinetobacter and human Rhinovirus/Enterovirus. High β-d-glucan fungal antigen suggested a severe fungal infection. To alleviate “cytokine storm” the patient was treated with hemoadsorption (CytoSorb) with transitory hemodynamic stabilization and improved graft function. Despite the therapy with wide-spectrum antibiotics, antiviral and antifungal drugs, the patient developed respiratory failure and need of mechanical ventilation and died on the 15th day of hospitalization. Conclusions. Rituximab and therapeutic plasma exchange are effective for FSGS recurrence following KTx. In these patients, the infections are usually caused by multiple microorganisms, and the diagnosis is challenging, because the clinical presentation is non-specific and the diagnostic tools have limited sensitivity and specificity. The mortality is very high despite the treatment.
Keywords: focal segmental glomerulosclerosis; kidney transplant; plasma exchange; fungal infection